Histone Posttranslational Modifications and Chromatin Remodelers in Prostate Cancer - Quintela Vieira, Ana Filipa (2019)
Prostate cancer (PCa) is one of the most incident and prevalent cancers in men worldwide and a leading cause of cancer-related morbidity and mortality. Epigenetics plays an important role in prostate carcinogenesis, namely abnormal expression of histone modifier enzymes and related chromatin modifications. Notwithstanding, the limited knowledge of the specific role of deregulated activity/expression of histone modifiers and respective histone modifications hinders their use in clinical management, particularly for PCa detection and prognostication. Due to the limitations in the analysis of global patterns of histone modifications, few studies reported on the biomarker potential of these epigenetic marks. Importantly, the reversible nature of histone modifications makes them a promising therapeutic option for this malignancy. Indeed, over the past years, molecules with inhibitory activity upon the epigenetic machinery have been developed and are currently under evaluation in clinical trials to test their effectiveness.